Determination of optimal island regions with simultaneous DG allocation and reconfiguration in power distribution networks - Cikan, Murat; Cikan, Nisa Nacar; Kekezoglu, Bedri (WILEY, 2025)
The rising demand for electric energy and environmental pollution concerns have led to using renewable energy-based distributed generators (DGs) in power distribution networks (PDN). However, the power flow may become bidirectional (non-radial) by introducing the DGs into the system, which may cause instability in the system's operation. System instability causes an increase in system losses and implies a rising in costs. This paper proposes a methodology using Moth Flame Optimizer and Equilibrium Optimizer to reconfigure the PDN, optimizing the siting, sizing, and power factor of multiple DGs to maintain radial mode operation. Determining DGs' allocation within a radial system by optimizing multi-parameters simultaneously leads to minimizing losses, enhancing reliability, and improving the stability of the network. Thus, the number of affected customers in a catastrophic power outage or emergency blackout scenarios can be minimized. The method has been tested on a 33-bus distribution system where four different scenarios with three cases for each are studied to show the performance of the proposed method. The method's effectiveness is demonstrated by minimizing power loss, enhancing the voltage stability index, assuring reliability, and improving the voltage profile. Moreover, the accuracy of reliability index calculation results is confirmed with the commercial software ETAP.
Keywords: renewable energy sources; resource allocation; DISTRIBUTION-SYSTEMS; LOSS MINIMIZATION; LOSS REDUCTION; MULTIOBJECTIVE RECONFIGURATION; RELIABILITY IMPROVEMENT; GENERATION ALLOCATION; ALGORITHM; OPTIMIZATION; LOSSES; INTEGRATION; Science & Technology - Other Topics; Energy & Fuels; Engineering